Construction Work Sequencing and Zoning Strategy for Structural Works at Summarecon Mall Bandung - Hafizul Adib Zulyan; Nevy Sandra (Universitas Negeri Padang, 2025)
Large building projects require a construction sequence that integrates technical dependencies, site access, material flow, and crew allocation. This study analysed the implementation of structural work sequencing and a zoning system in the Summarecon Mall Bandung Phase 2 project. A descriptive case-study approach was used. Data were obtained from project documents, shop drawings, field observations, and photographic documentation produced during the 2023 construction period. The analysis identified the logical dependencies between work packages and examined how six work zones were released. The structural sequence consisted of pile driving, pile-head cutting, excavation and backfilling, soil compaction, pile-cap and tie-beam construction, column works, and beam-and-slab works. Zones 1 and 5 were started first because they did not interfere with the main access and equipment manoeuvring areas. Zones 2 and 3 followed when the first zones reached approximately 30% progress. Zones 4 and 6 were completed last because they functioned as the principal access and logistics corridors. The zoning strategy enabled overlapping activities while maintaining access, but its effectiveness depended on labour competence, material delivery, equipment availability, approvals, financing, and site coordination. The study concluded that explicit access constraints and progress-based release rules should be included in structural work-sequencing plans.